“Estudio de factibilidad servicios de Parque Logístico CAM S.A.S” para parqueadero de vehículos de carga pesada en el distrito de Buenaventura (2014)
This assignment shows the feasibility of a Logistics center services project at Buenaventura district, based on port logistics sector needs analysis, making evident the big influence of heavy duty vehicles and logistics operations where parking zones are required for heavy duty vehicles and perform maneuvers of merchandises, having own equipment to guarantee safety and efficiency with times to perform different logistics operations. It was used theoretical framework made by Rodrigo Varela and presented by Henry Mitzberg in his book “Strategic process”, which has as structure besides of the procedures included in the project, the way an entrepreneur should define his policies, action plans, measure of the same and phases of the project; the methodology applied as a type of investigation is descriptive study and deductive investigation method. “Logistics center CAM S.A.S.” offers its heavy duty vehicles parking service and a specialized zone for packaging and unpacking, services for drivers, cargo importers and exporters, transportation companies, customs and maritime agencies; implementing the planning, organization, direction and control processes, a highly efficiency with brand new technology and highly qualified personnel working for the company. Allowing to offer costumers due service for all performed operations. The marketing realized showed positive information to supply all logistics chain needs in the sector, starting new logistics center which is economically profitable and will generate direct and indirect employments at Buenaventura district, adding professional and personal growing for all people who participates in this project.